Satuan Pengamanan (SATPAM) sebagai Mitra Kepolisian dalam Penanggulangan Keamanan Ketertiban Masyarakat di Kota Kupang - Angerius Agustinus Bria; Korolus Kopong Medan; Dhesy A. Kase (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
The authority and role of security guards assist the Police in carrying out security duties in a limited manner. The results of the study show that security guards in carrying out security responsibilities as a partner of the Police in dealing with and limited public order in the city of Kupang such as arresting the perpetrators of iron theft at PT Semen Kupang, Helmet Theft at the Kupang Polytechnic Campus, computer theft at the UKAW Kupang Campus and Oesapa Procurement Office Motorcycle Theft. Obstacles in carrying out duties and authorities as security guards include the authority of security guards which are limited by the law and inadequate facilities and infrastructure. Conclusion on the research Based on the provisions of Law number 2 of 2002 concerning the National Police of the Republic of Indonesia, it gives limited authority 'to security guard members to carry out security in the company environment acting Pre-emptive (fostering, directing), preventive (preventing, counteracting) and as limited law enforcement officers to assist the role of the functions of the National Police in a Repressive, Non-Judicial manner (acting, arresting, handcuffing, conducting initial interrogation) and in carrying out their duties and responsibilities the security guard experiences several obstacles such as the authority of the security guard which is limited by the law when he is in a position to face the perpetrator of the crime of theft who holds a weapon while the security guard officer is not armed because his authority is not like a member of the Police, but if the security guard officer resists it will be suspected that he has committed an unlawful act because of his limited authority and the law and the Facilities and Inadequate infrastructure.